Altered Expression of Glial Gap Junction Proteins Cx43, Cx30, and Cx47 in the 5XFAD Model of Alzheimer’s Disease - Angeli, Stella; Kousiappa, Ioanna; Stavrou, Marios; Sargiannidou, Irene; Georgiou, Elena; Papacostas, Savvas S.; Kleopa, Kleopas A. (Frontiers in Neuroscience, 2020)
Glial gap junction proteins, called connexins (Cxs), form gap junctions in the central nervous system to allow the bidirectional cytosolic exchange of molecules between adjacent cells. Their involvement in inheritable diseases and the use of experimental animal models that closely mimic such diseases revealed the critical role of glial GJs in myelination and homeostasis. Cxs are also implicated in acquired demyelinating disorders, such as Multiple Sclerosis (MS) and Alzheimer’s disease (AD). Animal and human studies have revealed a role of the astrocytic Cx43 in the progression of AD but the role of Cx47, which is the main partner of Cx43 in the astrocyte-oligodendrocyte GJs is still unknown. The aim of this study was to investigate the astrocytic connexins, Cx43 and Cx30 in relation to oligodendrocytic Cx47 in the cortex and thalamus of the 5XFAD mouse model of AD. The model was characterized by increased Aβ deposition, gliosis, neuronal loss, and memory impairment. Compared to wild-type mice, Cx43 and Cx30 showed increased immunoreactivity in older 5XFAD mice, reflecting astrogliosis, while Cx47 immunoreactivity was reduced. Moreover, Cx47 GJ plaques showed reduced colocalization with Cx43 plaques. Oligodendrocyte precursor cells (OPCs) and mature oligodendrocyte populations were also depleted, and myelin deficits were observed. Our findings indicate reduced astrocyte-oligodendrocyte gap junction connectivity and possibly a shift in Cx43 expression towards astrocyte-astrocyte gap junctions and/or hemichannels, that could impair oligodendrocyte homeostasis and myelination. However, other factors, such as Aβ toxicity, could directly affect oligodendrocyte survival in AD. Our study provides evidence that Cxs might have implications in the progression of AD, although the role of oligodendrocyte Cxs in AD requires further investigation.